2017
DOI: 10.1002/ecs2.1703
|View full text |Cite
|
Sign up to set email alerts
|

Discordant response of spider communities to forests disturbed by deer herbivory and changes in prey availability

Abstract: Citation: Landsman, A. P., and J. L. Bowman. 2017. Discordant response of spider communities to forests disturbed by deer herbivory and changes in prey availability. Ecosphere 8(2):e01703. 10.1002/ecs2.1703Abstract. Despite the breadth of research on impacts of dense ungulate populations and invasive plants on native vegetation, work involving indirect effects on spider communities is explicitly lacking. Forest spiders depend on palatable insect prey and habitat structure, both of which are affected by herbivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…For example, many of the dipteran species we collected belonged to taxa from detrital food webs, such as many within the Mycetophilidae. These results are similar to past research on the benefit of invasive plant species specifically to detrital communities (McCary et al., 2016) and the importance of plant structure to spider communities (Landsman & Bowman, 2017; Miyashita, Takada, & Shimazaki, 2004; Takada, Baba, Yanagi, Terada, & Miyashita, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, many of the dipteran species we collected belonged to taxa from detrital food webs, such as many within the Mycetophilidae. These results are similar to past research on the benefit of invasive plant species specifically to detrital communities (McCary et al., 2016) and the importance of plant structure to spider communities (Landsman & Bowman, 2017; Miyashita, Takada, & Shimazaki, 2004; Takada, Baba, Yanagi, Terada, & Miyashita, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…These Our findings may be restricted to those areas with high ungulate densities and resulting depauperate understory vegetation: Deer densities in our sampling area were between 46 and 66 deer/km 2 while densities at much lower levels can cause significant impacts to understory forest vegetation and structure (Horsley, Stout, & de Calesta, 2003;Tilghman, 1989). Vegetation structure is a critical factor affecting the ability of a habitat to support understory spiders in forests with extensive ungulate herbivory (Landsman & Bowman, 2017;Miyashita et al, 2004;Takada et al, 2008). In habitats where additional native or non-native structure exists, the relationship between M. vimineum and the invertebrate community could reverse, as was noticeable in the Antietam plot pair and evident in the significance of the interaction term between Park and plant invasion on many of the response variables.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…and some other insect pest species (Betz & Tscharntke, 2017). Spider diversity is significantly dependent on vegetation structure (Landsman & Bowman, 2017). The species richness and abundance of spiders are higher in the abandoned fields in which more plant species grown than in rice fields (Baba, Tanaka, & Kusumoto, 2019).…”
Section: Species Richness and Abundancementioning
confidence: 99%
“…Research has shown that intense grazing of forest understory vegetation will lead to decreased understory height as well as changes in understory composition in boreal forest (Speed et al, 2014;Lorentzen Kolstad et al, 2018). Other studies investigating the subsequent effects of browsing on arthropod communities observed a change in both diversity and composition (Suominen et al, 1999;Landsman and Bowman, 2017;Lilleeng et al, 2018). One consequence of an altered predator community is subsequent effects on predation rates of insect herbivores, and plant damage levels.…”
Section: Introductionmentioning
confidence: 99%